Estudio socioeconómico de beneficiarias del bono del desarrollo humano acogidas al programa de inclusión económica del MIES en el recinto Loma de Coco del cantón Quinsaloma - López Vidal, Astrid Samanta (2018)
The present research is titled "Socio-economic study of beneficiaries of the human development bond under the economic inclusion program of MIES in the Loma de Coco Campus of the canton Quinsaloma", was carried out with the purpose of diagnosing the socioeconomic situations experienced by the beneficiaries of the bonus of human development in the rural sector and its entrepreneurship in agricultural activities, through an agreement with the Ministry of Economic and Social Inclusion with the Banecuador, within the objectives that define the object of study we have; Analyze the socioeconomic aspects of beneficiaries of the human development bonus of the economic inclusion program of the MIES of the Loma de Coco enclosure of the Quinsaloma canton and establish the main needs of public and private institutions of the families immersed in the economic inclusion program. The study methods were the analytical, deductive and statistical that allowed collecting timely and accurate information through the survey technique with questions in relation to the objectives raised in the research while the type of research was exploratory, descriptive and explanatory. . During the research process, scientific, concrete and theoretical data were obtained from different authors who refer to the main topic; The majority of beneficiaries coexist in Unión Libre, they self-identify as montuvias, they have lived in the sector for more than five years, 62% have their own house but most of them are cane or mixed, all the houses have between one and two rooms, that is, they live in overcrowding considering that they all have children under their care, of which most are minors and 38% of those surveyed depend exclusively on the bonus; Therefore, it can be asserted that all people who receive the Human Development Bond live in poverty conditions and 69% of them claim that the loan helped them improve their lifestyle. Key Words: Socioeconomic Study, Human Development Bond, Economic Credit.